2019
DOI: 10.1590/1806-90882019000100005
|View full text |Cite
|
Sign up to set email alerts
|

Regional Concentration of Charcoal Production in the State of Paraíba, Brazil (1994 - 2016)

Abstract: Charcoal has an economic, social and environmental importance, because in addition to being a source of energy, it generates employment and income in the rural environment. Therefore, knowing your market is fundamental for the decision-making of those segments that depend on this raw material. This work analyzed the regional concentration of charcoal production in the state of Paraíba, Brazil, from 1994 to 2016. The data used to measure the regional production concentration (in tons) of native Paraíba charcoal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
1
0
4
Order By: Relevance
“…Porém, nas últimas décadas, houve uma intensificação do desmatamento desse bioma para outros fins, especialmente para a implantação de atividades agropecuárias (Souza et al, 2021). Ainda, a redução na produção de carvão vegetal nas últimas décadas é reportada em todo o Estado da Paraíba, o que está associado à diminuição dos estoques madeireiros das florestas do Estado (Coelho Junior et al, 2019). industrial.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Porém, nas últimas décadas, houve uma intensificação do desmatamento desse bioma para outros fins, especialmente para a implantação de atividades agropecuárias (Souza et al, 2021). Ainda, a redução na produção de carvão vegetal nas últimas décadas é reportada em todo o Estado da Paraíba, o que está associado à diminuição dos estoques madeireiros das florestas do Estado (Coelho Junior et al, 2019). industrial.…”
Section: Resultsunclassified
“…Posteriormente, essa matriz de dados foi submetida a uma Análise de Componentes Principais (ACP). Essa categoria de análise é um método estatístico que permite reduzir um grande número de variáveis possivelmente correlacionadas a um conjunto menor de componentes não correlacionados, permitindo assim revelar a estrutura interna dos dados para melhor explicar as variações nos dados em análise (Congreves et al, 2015). A ACP foi obtida a partir do pacote FactoMineR (Factor Analysis e Data Mining com R) (LÊ et al, 2008) no software R versão 3.6.1 (R Core Team, 2021).…”
Section: Methodsunclassified
“…Traves do índice de Theil, e outros índices, foi encontrado uma grande concentração para o número de usinas, principalmente no Sudeste do país. Outros trabalhos sobre recursos energéticos brasileiros que usam o índice de Theil são Scheffer (2016), Coelho et al (2019), Júnior et al (2017) e Júnior et al (2018.…”
Section: Referencial Teóricounclassified
“…Coelho junior (2016) verified the regional concentration of pinhão in the State of Paraná. Filgueiras et al (2017) observed the log wood market in the State of Pará and Coelho junior et al (2018b, 2019a, 2019b reported on the concentration of the firewood market in the State of Paraíba…”
Section: Introductionmentioning
confidence: 99%